Impact of the Zonal Flows on the Relative Short-Scale ULF Electromagnetic Waves in theShear Flow Driven Ionosphere - Chargazia, Khatuna (Journals of Georgian Geophysical Society, 2018)
Influence of the large-scale zonal flows and magnetic fields on the relative short-scale ULF electromagnetic waves in the dissipative ionosphere in the presence of a smooth inhomogeneous zonal wind (shear flow) is studied. A broad spectrum of Alfvenic-like electromagnetic ﬂuctuations appears from electromagnetic drift turbulence and evidence of the existence of magnetic ﬂuctuations in the shear ﬂow region is shown in the experiments. In present work one possible theoretical explanation of the generation of electromagnetic ﬂuctuations in DW-ZF systems is given. For shear flows, the operators of the linear problem are non-selfconjugate and therefore the eigenfunctions of the problem are non-normal. The non-normality results in linear transient growth with bursts of the perturbations and the mode coupling, which causes the generation of electromagnetic waves from the drift wave–shear ﬂow system. We show that the transient growth substantially exceeds the growth of the classical dissipative trapped-particle instability of the system. Excitation of electromagnetic ﬂuctuations in DW-ZF systems leads to the Attenuation-suppression of the short-scale turbulence